Basic medical sciences and understanding medicine: Insights from medical students - Dima Alhomsi; Mhd Khaled Tello; Dania Abdalsalam; Majd Barmo; Hamzeh Al Asadi; Hasan Najjar; Bayan Alsaid (PLoS ONE, 2025)
Introduction Basic medical sciences form the cornerstone of any medical knowledge and are essential for understanding various diseases. This study aims to shed light on students’ viewpoints toward those sciences while delving into their motivations and hindrances and investigating individual subjects. Methods This cross-sectional study was carried out at Damascus University in Syria, targeting final-year medical students. Data collection occurred on a designated clerkship day, during which students were invited to complete an anonymous, self-administered questionnaire. The questionnaire evaluated students’ overall perception and academic interest in studying basic medical sciences in pre-clinical years and their willingness to pursue these sciences as a prospective career. Results The study surveyed 350 medical students, with 40% rating their interest as good/very good. The extensive content was perceived as a major hindrance by 76.9%. Anatomy was perceived as the easiest subject while pharmacology and biochemistry were considered the hardest. The majority acknowledged the value of basic sciences for further medical education (75.1%) and good physician (77.4%), but only 20.9% indicated their relevance for practical training. Furthermore, 68.6% of students were not interested in pursuing these sciences as a career, primarily due to their preference for clinical fields (55.8%) and concerns about low-income potential (41.3%). Conclusion This study highlighted students’ positive views on Basic Medical Sciences, emphasizing their essential role in understanding disease pathophysiology for medical education and practice. Nonetheless, it pointed out a lack of practical training. The findings underscore the importance of decreasing content intensity and enhancing retention through practical approaches aligned with clinical practice.